E-Book-Based Group Counseling with Contingency Contracting to Reduce Bullying Among Islamic Boarding School Teenagers - Wahyu Almizri; Firman Firman; Yeni Karneli (STAI Hubbulwathan Duri, 2024)
Bullying among teenagers in Islamic boarding schools poses significant challenges to student well-being and academic environments. This study investigates the effectiveness of behavioristic group counseling, utilizing contingency contracting strategies, to reduce bullying behaviors. A single-case experimental AB design was employed, involving ten eighth-grade students from Islamic boarding schools. Data were collected using validated youth instruments specific to the context of Islamic boarding schools. The intervention's impact was analyzed using the Wilcoxon Signed Ranks t-test to compare pretest and posttest bullying behavior scores. Statistical analysis revealed significant reductions in bullying behaviors among the participants following the intervention. All ten respondents in the experimental group demonstrated notable declines in bullying behavior scores from the baseline (pretest) to the intervention period (posttest). These findings indicate the efficacy of group counseling with contingency contracting strategies in mitigating bullying behaviors. The results support the potential of behavioristic group counseling as an intervention to address bullying among teenagers in Islamic boarding schools. The observed reductions in bullying behaviors highlight the utility of contingency contracting strategies as a targeted approach in educational settings. Group counseling with contingency contracting strategies effectively reduces bullying behavior in Islamic boarding schools. Future research with larger and more diverse samples is recommended to generalize these findings and explore additional contextual factors influencing intervention success.